Avaliatividade e conjunção em textos argumentativos de uma coleção didática de linguagens e suas tecnologias: estudo com base em gênero na perspectiva da LSF - Barros, Guilherme Barbat (2024)
Evaluating. According to Martin and Rose (2008), this is one of the three main purposes for which we use language. And it is on this the investigation of this dissertation, anchored in the systemic functional perspective (HALLIDAY; MATTHIESSEN, 2014), is focused. Thus, the main objective is to analyze occurrences of the discourse systems of APPRAISAL (MARTIN; WHITE, 2005; MARTIN; ROSE, 2007) and CONJUNCTION (MARTIN; ROSE, 2007) that contribute for the realization of the Genre Schematic Structure in texts with argumentative potential present in a collection of textbooks of Portuguese Language and of Linguagens e suas Tecnologias for High School. For the selection of the textbook collection as universe of analysis, the subsequent criteria were followed: having been approved by Programa Nacional do Livro e do Material Didático, being used in the host city of the institution where this research is carried out, and having copies with available access for the researcher. For the selection of the corpus of analysis, texts with the potential of instantiating genres from the family of arguments were sought, according to the characteristics pointed out by Martin and Rose (2008) and Rose (2011). After this survey, other two criteria were considered: not being speech transcriptions, and not having been fragmented. Applied these criteria, the corpus was constituted of ten texts. The linguistic analyses of the already mentioned discourse systems confirm the purpose of presenting a point of view in all of the texts from the corpus, and the Genre Schematic Structure is constituted, as predicted by the bibliography, of the stages Thesis, Arguments and Restatement. As for the phases, besides the arguments 1, 2, and, at times, 3, linguistic marks of realization of the phases contextualization, generalization, arguments preview, proposal and effect were also found. Moreover, through the analysis of the occurrences of APPRAISAL and CONJUNCTION, based on the lexicogrammatical systems of transitivity and MODE, subphases are proposed to the Exposition genre: setting, exemplification, quotation, reflection, synthesis, demand, activity, aim, cause, consequence, expectation, preview, comment, and problem. In the analyzed corpus, the most recurrent subphases were problem, realized by negative APPRAISAL and, occasionally, by external conjunctions of comparison–contrast; cause, realized by external conjunctions of consequence–cause; and exemplification, realized by internal conjunctions of comparison–similarity.